Pengembangan Bahan Ajar Menulis Teks Prosedur Kompleks Dengan Model Pembelajaran Discovery Learning Menggunakan Media Audio Visual (Video) Di Kelas XI SMA Negeri 1 Samarinda - Paramita Candra Devi; Yusak Hudiyono; Widyatmike Gede Mulawarman (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2018)
This study aims to develop text learning materials to write complex procedures with learning discovery learning model using audio visual media (video). The research form used is research and development method (R&D). The design used in the research and development of this teaching material adopted from Borg and Gall design model. This development research was conducted in SMA. The result of validation of this teaching material proved to be valid with the average of validation of content (material) 82% said valid, validation of 100% validity of the linguist, and the validation result of the media expert on the 93% video assessment stated very valid and on the handbook rating 84% students stated very valid. The results of the class XI test of SMA showed 86% stated very valid. From the result of data analysis through t-test formula yield Thitung (13,68)> ttabel (1,703), so there is cognitive difference between before and after student use instructional material developed in book with learning discovery learning modeling using audio-visual media with material text of complex class XI procedures. Then the results of the development that has been done to improve student learning outcomes.